Early-Pregnancy Changes in Maternal Lipid Profile in Women with Recurrent Preeclampsia and Women with Normal Pregnancy - Saihood, Sumaya T. (Journal of the Faculty of Medicine Baghdad, 2017)
Background: “According to the current knowledge, changes in lipid profile in pregnancy is a major contributor in the pathogenesis of preeclampsia. The present study was designed to compare the changes in lipid profile in normal pregnancy and in patients with history of recurrent pre-eclampsia (PE).” Objective: Assessment the relationship between lipid profiles changes in women with history of recurrent preeclampsia in comparison to normal pregnancy in early pregnancy. Patients and Methods: Measurement of lipid profile changes in women with history of recurrent preeclampsia (more than two preeclampsia in previous pregnancies) at 12 to 16 weeks of pregnancy and compared to normal pregnancy as a control group who does not have history of preeclampsia also early in pregnancy Results: The patients with history of recurrent Preeclampsia had significantly higher mean total cholesterol level compared to controls (216.1 ± 25.5 mg/dl) and (195.6 ± 23.2 mg/dl), respectively, (P<0.05).The mean HDL cholesterol (HDL-C) level was significantly lower in PE group (49.3 ± 9.2 mg/dl) than controls (52.2 ± 8.4 mg/dl), (P<0.05). The mean level of LDL cholesterol was (122.3 ± 28.7) mg/dl in PE group and it was significantly higher than the (108.6 ± 26.8 mg/dl) of controls, (P<0.05). Similarly, the mean VLDL cholesterol was also higher in women with history of recurrent preeclampsia than control group, (44.8 ± 12.6) vs. (34.8 ± 7.3) mg/dl, respectively, (P<0.05). The Triglycerides (TG) was also elevated in women with history of recurrent preeclampsia where the mean TG level was (224.2 ± 63.1 mg/dl) compared to (174.6 ± 36.3mg/dl) in controls, (P<0.05). Conclusion: “This study showed that the women who have history of recurrent preeclampsia had disturbed lipid profile (increased levels of total TC, TG, VLDL-C and LDL-C concentration) in addition to decrease the high density lipoprotein cholesterol (HDL-C) level in subsequent pregnancy compared to normal pregnancy.”